World Bank Support for Open Data 2012-2017 - World Bank Group (World Bank, Washington, DC, 2017)
This report summarizes the World Bank’s activities to support the Open Data efforts of developing countries during the period 2012 - 2017. It is largely descriptive, but Chapter 4 includes key analysis and lessons learned. The main objectives of this report are to share information within the World Bank and with its partners and client countries, and to preserve the institutional memory and highlight the lessons learned as a way to improve the development effectiveness of Open Data.